A prospective, randomized, single‐blinded trial for improving health outcomes in rhinology by the use of personalized video recordings. Issue 12 (17th September 2018) - Sharma, Saurabh; McCrary, Hilary; Romero, Erin; Kim, Alexander; Chang, Eugene; Le, Christopher H
Abstract : Background: Clear patient‐physician communication is critical in improving patient compliance, outcomes, and satisfaction. However, constraints of shortened clinic visits, patient anxiety, and poor recall can cause significant barriers to effective communication. We hypothesized that the ability to view patient‐physician counseling videos at home would improve health outcomes. Methods: Patients in a tertiary rhinology clinic were enrolled into a single‐blinded prospective study after obtaining institutional review board (IRB) approval and informed consent. All enrollees had a short summary of their clinical encounter video‐recorded with a tablet using Medical Memory, a Health Insurance Portability and Accountability Act (HIPAA)‐compliant software system. Patients were randomized to receive access to their videos by our research coordinator, and outcomes included questionnaires at the first postoperative visit to assess patient recall and satisfaction. Results: A total of 101 patients were enrolled. Half of those with video access watched the video at least once, on average 3.44 times. Of those without access, 90% would have liked the option. Those with video access had a higher percentage of correct answers to questions regarding surgical risk and extent of surgery; however, there was no significant difference between the 2 groups. Conclusion: Our results show that patients in both groups were enthusiastic about this technology and often shared their videos with family and friends. Video‐recordings of physician‐patient encounters may be a possible solution to improve physician‐patient communication.